European Energy Markets Observatory (2008) 2007 and Winter 2007/2008 Data Set - Tenth Edition, November 2008 - Lewiner, Colette (Springer Netherlands : Imprint: Springer, 2010)
Capgemini's European Energy Markets Observatory (EEMO) is an annual report that tracks the progress in establishing an open and competitive electricity and gas market in EU-27 (+ Norway and Switzerland) as well as the progress on the EU Climate-Energy package objectives. Launched in 2002 with the primary objective to assess the progress of deregulation in the European Member States, the report now tackles all the major issues faced by the Utilities industry. Through 70+ indicators, the report scans all the segments of the value chain and analyses the hot topics of the moment, to identify the key trends in the electricity and gas industries. The report includes country focus, highlighting the local key issues, and topic focus on leading-edge themes. Capgemini's partners - Société Générale Global Research and Strategy for their expertise in financial analysis, VaasaETT for their in-depth knowledge of customers' behaviours and CMS Bureau Francis Lefebvre for their understanding of European energy policies and instances - enrich the report on their respective area of expertise. The 10th edition of the European Energy Markets Observatory (EEMO) covers the full year 2007 and the winter 2007/08. The key findings include: -Oil price increase in 2007 and H1 2008 exacerbated fundamental tensions in the industry. The present price drop poses other problems. -Limited progress has been made to solve the "reducing CO2 emissions / satisfying the energy demand" equation, but there are reasons to hope. -After an interim improvement in 2006, electricity security of supply deteriorated in 2007, calling for a significant investment program. -Geopolitical tensions have increased risk on gas security of supply. -Progress was made towards a common electricity market in Europe, but competition is not really taking up and prices to end customers skyrocketed in early 08. -The Utilities are in a good financial situation and important M&A have landed in 2008. -The financial and economic crisis is impacting the Utilities industry and should accelerate their business model change.